ANALISIS RASIO LIKUIDITAS, AKTIVITAS, SOLVABILITAS, DAN PROFITABILITAS UNTUK MENILAI KINERJA KEUANGAN - Fanalisa, Fauziyah; Juwita, Himmiyatul Amanah Jiwa (Jurnal Management Risiko dan Keuangan, 2022)
The objective of this descriptive quantitative research is to identify the financial performance of PT. Angkasa Pura II (Persero) during the 2018-2020 period using time-series financial ratio analysis. Ratio analysis is a method that identifies relationships between certain posts in balance sheets, individual profit-and-lost statements, and the combination of the two. The variables used in this study are liquidity ratio, i.e. current ratio and quick ratio; activity ratio, i.e. inventory turnover ratio, fixed assets turnover ratio, and total assets turnover ratio; solvability ratio, i.e. debt-to-asset ratio and debt-to-equity ratio; and profitability ratio, i.e. net profit margin, return on assets, and return on equity. This study finds that firm’s liquidity was unfavorable, or not liquid. This is reflected from its current and quick ratios that show risks in the company’s capability to pay its short-term liabilities, evidenced by the decreasing values of the two ratios during the research period. The company’s activity ratio was also not very good since its inventory turnover ratio, fixed assets turnover ratio, and  total assets turnover ratio were also decreasing. This means that the company had not been able to use its assets effectively to increase its revenue. In terms of solvability, increases in debt-to-asset ratio and debt-to-equity ratio inform that the company had a great financial risk that accompanies its huge chances to produce high profit. Finally, the company’s profitability was also not good because declining trends were found in its net profit margin, return on assets, and return on equity, indicating that the company had suffered losses and had not been able to generate profit from all its capacities and resources.